2019
DOI: 10.1371/journal.pone.0210077
|View full text |Cite
|
Sign up to set email alerts
|

The FXR agonist obeticholic acid inhibits the cancerogenic potential of human cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is an aggressive cancer with high resistance to chemotherapeutics. CCA is enriched in cancer stem cells, which correlate with aggressiveness and prognosis. FXR, a member of the metabolic nuclear receptor family, is markedly down-regulated in human CCA. Our aim was to evaluate, in primary cultures of human intrahepatic CCA (iCCA), the effects of the FXR agonist obeticholic acid (OCA), a semisynthetic bile acid derivative, on their cancerogenic potential. Primary human iCCA cell cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 56 publications
1
37
1
Order By: Relevance
“…Cell proliferation was assessed by 3‐(4,5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2 H ‐tetrazolium (MTS) assay, DNA Quantification (see the Supporting Information), and population doubling time (PDT) . Cell migration has been assessed by a scratch test …”
Section: Methodsmentioning
confidence: 99%
“…Cell proliferation was assessed by 3‐(4,5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2 H ‐tetrazolium (MTS) assay, DNA Quantification (see the Supporting Information), and population doubling time (PDT) . Cell migration has been assessed by a scratch test …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, many research groups are studying several strategies to block CSCs activity, the cells responsible for tumour growth, recidivism and chemoresistance (1,9,25). Currently the drug therapy via radio-chemo-therapy is primarily for palliative purposes because it does not target CSCs (19,26). In fact, surgical resection is the only effective therapy but it is low applicable given the numerous late diagnoses(1).…”
Section: Discussionmentioning
confidence: 99%
“…As described in previous papers (9,19), pCCA and iCCA were selected and cultured in H69 medium and used for experiments over 30 passages from isolation.…”
Section: Accepted Articlementioning
confidence: 99%
“…FXR usually express on the surface of liver cells and bile duct cells, and its function is to transport bile acid. Therefore, FXR plays an important role in bile-acid excretion, bile-acid concentration stabilization, and the reabsorption process of bile acid enterohepatic circulation [7][8][9][10]. We previously found that bile salt export pump (Bsep), a target gene of FXR,expression decreased in hilar cholangiocarcinoma tissues of rats.…”
Section: Discussionmentioning
confidence: 99%